2015
DOI: 10.1007/s10565-016-9312-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of apoptosis induction by Gaillardin, a sesquiterpene lactone, in breast cancer cell lines

Abstract: Medicinal plant extracts have been widely used for cancer treatment. Gaillardin is a natural sesquiterpene lactone that has recently been reported to have anticancer properties. The ability to induce apoptosis is an important property of a candidate anticancer drug, which discriminates between anticancer drugs and toxic compounds. The current study was therefore carried out to address the issue if Gaillardin is able to induce apoptosis in the breast cancer cell lines MCF-7 and MDA-MB-468 and to determine the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Wei et al [33] found that miR-497-mediated BCL-2 degradation resulted in suppressed proliferation of breast cancer cells. Similar results were observed in research carried out by Fallahian et al [34] and Li et al [35] found that BCL-2 downregulation increased apoptosis in breast cancer cells. Hence, we found BCL-2 to be an attractive target for further research.…”
Section: Discussionsupporting
confidence: 91%
“…Wei et al [33] found that miR-497-mediated BCL-2 degradation resulted in suppressed proliferation of breast cancer cells. Similar results were observed in research carried out by Fallahian et al [34] and Li et al [35] found that BCL-2 downregulation increased apoptosis in breast cancer cells. Hence, we found BCL-2 to be an attractive target for further research.…”
Section: Discussionsupporting
confidence: 91%
“…31,32) ROS participates in P53-mediated mitochondrial apoptosis through regulating mitochondrial membrane potential and inducing Cyto C release and activation of caspase cascades. [33][34][35] In addition to ROS, P53 could activate mitochondrial pathway through regulation of Bax and Bcl-2 family members. [36][37][38] The results in the current study showed that downregulation of miR-30 promoted ROS generation through activation of P53.…”
Section: Discussionmentioning
confidence: 99%
“…At least 10,000 cells were analyzed for each sample. The apoptosis rate was calculated using the following formula 14 : Apoptosis rate (%)=(Number of apoptotic cells/Number of total cells observed)×100.…”
Section: Methodsmentioning
confidence: 99%